2018
DOI: 10.1126/science.aao0335
|View full text |Cite
|
Sign up to set email alerts
|

Random heteropolymers preserve protein function in foreign environments

Abstract: The successful incorporation of active proteins into synthetic polymers could lead to a new class of materials with functions found only in living systems. However, proteins rarely function under the conditions suitable for polymer processing. On the basis of an analysis of trends in protein sequences and characteristic chemical patterns on protein surfaces, we designed four-monomer random heteropolymers to mimic intrinsically disordered proteins for protein solubilization and stabilization in non-native envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
285
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(302 citation statements)
references
References 51 publications
(29 reference statements)
6
285
0
Order By: Relevance
“…All the covalent bonds were constrained, which supported an integration time step of 2.5 fs. These parameters were recommended for the accurate reproduction of the original CHARMM simulation on lipid membrane system 38 and were verified in simulations on proteins 20,39,40 and lipid membranes 41 . The production simulation lasted 100 ns.…”
Section: Figure 4 Simulation Methods In the Absence (B-e) And Presencmentioning
confidence: 95%
“…All the covalent bonds were constrained, which supported an integration time step of 2.5 fs. These parameters were recommended for the accurate reproduction of the original CHARMM simulation on lipid membrane system 38 and were verified in simulations on proteins 20,39,40 and lipid membranes 41 . The production simulation lasted 100 ns.…”
Section: Figure 4 Simulation Methods In the Absence (B-e) And Presencmentioning
confidence: 95%
“…Strikingly, in the presence of Hero45, EGFP fluorescence remained undiminished even in chloroform ( Figure 3C). This is reminiscent of the ability of methacrylate-based random heteropolymers (RHPs) to preserve horseradish peroxidase (HRP) activity in toluene (Panganiban et al, 2018). Thus, naturally occurring Hero proteins act as molecular shields to stabilize proteins, even against harsh conditions.…”
Section: Hero Proteins Protect the Activity Of Various Proteins Undermentioning
confidence: 99%
“…Given the sheer diversity of folded protein structure and surface chemistry, the idea of designing a specific interaction can be daunting. However, in a very exciting report, Xu and coworkers demonstrated that control over the statistical monomer distribution in a random heteropolymers allowed for creation of a chaperone-like polymer shell that improved protein stability in both water and organic solvents [88]. The statistical design of the heteropolymers was informed by analysis of the size and spacing between clusters of residues with the same properties (i.e., positive charge, negative charge, hydrophobic, and neutral hydrophilic) (Figure 3).…”
Section: Liquid-liquid Phase Separation: Segregation Purification Anmentioning
confidence: 99%